An investigation on dysfunction of local wisdom in development in Simalungun regency - Corry, Corry; Napitu, Ulung; Napitu, Resna; Herman, Herman; Van Thao, Nguyen (Research Journal in Advanced Humanities, 2025)
This study aims to analyze the sociocultural phenomenon of dysfunction and degradation of local wisdom in the implementation of development in Simalungun Regency. The research method used in this study is descriptive qualitative. Primary data were collected through field research by conducting in-depth interviews with informants. Secondary data were obtained through library research. The technique for selecting informants was purposive sampling with 16 selected informants representing government figures, community leaders, traditional leaders, religious leaders, and communities who have in-depth and specific knowledge of the problem being studied. Data analysis began with data collection activities, compiling interview transcripts, data tabulation, data presentation, data reduction, data classification, data interpretation and formulation of conclusions. The results of the study indicate that Simalungun local wisdom has an important role in optimizing the implementation of development in Simalungun Regency, but empirically, this local wisdom has experienced dysfunction and degradation in the implementation of development. Development in Simalungun Regency must involve all elements of society, optimize resource utilization, community empowerment, and re-function local wisdom with a cultural approach in the form of; Marharoan Bolon, Sapangambei Manoktok Hitei, Habonaron do Bona, Tolu Sahundulan Lima Saodoran, Marsialopari, Marsiurupan and other local wisdom in implementing development in Simalungun Regency.